F. Nietzsche’s Approach to Truth: A Deadly Bite? - Stepukonis, Aivaras (Problemos, 2004)
A requisite for a proper understanding of Nietzsche’s philosophy of truth is some acquaintance with the general way in which the thinker approaches most of his intellectual problems and which in many a detail resembles that of René Descartes and his methodic doubt. In Nietzsche’s thought, there may be observed a threefold turning away from the traditionally affirmative conception of truth: (1) the reduction of thinking and knowing to the physiological processes of the body and its changing corporeal states; (2) the exposure of many time-honoured truths as mere superstitions expedient to factual human communities in dealing with reality in a practical, yet oversimplified and distorted manner; (3) the devaluation and/or disvaluation of truth as something useless or even detrimental to life. In discussing Nietzsche’s conception of truth it is also important not to miss his inclination toward a genetic way of explanation, his pervasive interest, that is, in the historical, anthropological, and philological genealogy of moral and social phenomena.